The Chemical Properties of a Mixing of Palm Kernel Shell Charcoal and Coconut Shell Charcoal in Making Briquettes - hamka nurkaya; Diva Aprilia Yahya; Eva Nurmarini; Marwati (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
This study aims to make briquettes from palm shells and coconut shells and determine the chemical properties of mixing palm shells and coconut shells. The study was conducted using the Complete Random Design (RAL) method by testing water content, ash content, volatile matter, and fixed carbon. The mixing treatment of palm shells and coconut shells according to the ratio, namely P1 = palm shell:coconut shell (100:0), P2 = palm shell:coconut shell (75:25), P3 = palm shell:coconut shell (50:50), P4 = palm shell:coconut shell (25:75), P5 = palm shell:coconut shell (0:100). The results showed that the ratio of a mixture of palm shell charcoal and coconut shell charcoal had no significant effect on water content, ash content, and fixed carbon. However, differences in significance occur in volatile matter. P2, P3, P4, and P5 have met SNI standard No.1-6235-2000, but P1 has not met SNI standard No.1-6235-2000.